Prevalence of non-carious cervical lesions and cervical dentinary hypersensitivity in undergraduate students - João Victor Dias CRISÓSTOMO; Bruna Oliveira BEZERRA; Mariana Garcia da Ponte MELO; Polyanna Maria ROCHA-NOVAIS; Maria Denise Rodrigues de MORAES (Universidade Estadual Paulista, 2021)
Abstract Introduction The non-carious cervical lesion (NCCL) is currently a common oral disease. Objective This observational and descriptive study aimed to assess risk factors associated with non-carious cervical lesions, cervical dentin hypersensitivity (CDH), gingival recession (GR) and the relationship between these conditions in students in the last years of undergraduate dentistry. Material and method One hundred eighty-five dentistry students from a private college in Ceará with an average of 22.7 ± 2.3 years participated by filling out a google docs form. Two calibrated examiners performed the exams to verify the presence of NCCL, CDH and RG. Result The presence of NCCL was 22.7%, GR was 48.1% and cervical dentin hypersensitivity 8.6%. The chi-square test with p < 0.05% verified a correlation between the presence of NCCL and the presence of GR and CDH. 25% of students had NCCL and 14% considered themselves stressed. There was no association between the variables bruxism and stress (p=0.529), bruxism and year of graduation course (p=0.716), as well as no association between stress and year of course (p = 0.397) was observed. There were no correlations between NCCL and bruxism, muscle symptoms, parafunctional habits and temporomandibular dysfunction. 10.8% of students who reported using legal and illegal drugs had NCCL. Conclusion The NCCL, GR and CDH were correlated in the group of students in the last two years of an undergraduate dentistry course in Ceará.